Characterisation of patients with Glanzmann thrombasthenia and identification of 17 novel mutations - Sandrock-Lang, Kirstin; Oldenburg, Johannes; Wiegering, Verena; Halimeh, Susan; Santoso, Sentot; Kurnik, Karin; Fischer, Lars; Tsakiris, Dimitrios A.; Sigl-Kraetzig, Michael; Brand, Brigitte; Bührlen, Martina; Kraetzer, Katharina; Deeg, Niklas; Hund, Martin; Busse, Eileen; Kahle, Anja; Zieger, Barbara (Thrombosis and Haemostasis, 2015)
Glanzmann thrombasthenia (GT) is an autosomal recessive bleeding disorder characterised by quantitative and/or qualitative defects of the platelet glycoprotein (GP) IIb/IIIa complex, also called integrin αIIbβ3. αIIbβ3 is well known as a platelet fibrinogen receptor and mediates platelet aggregation, firm adhesion, and spreading. This study describes the molecular genetic analyses of 19 patients with GT who were diagnosed on the basis of clinical parameters and platelet analyses. The patients’ bleeding signs include epistaxis, mucocutaneous bleeding, haematomas, petechiae, gastrointestinal bleeding, and menorrhagia. Homozygous or compound heterozygous mutations in ITGA2B or ITGB3 were identified as causing GT by sequencing of genomic DNA. All exons including exon/intron boundaries of both genes were analysed. In a patient with an intronic mutation, splicing of mRNA was analysed using reverse transcriptase (RT)-PCR of platelet-derived RNA. In short, 16 of 19 patients revealed 27 different mutations (ITGA2B: n=17, ITGB3: n=10). Seventeen of these mutations have not been published to date. Mutations in ITGA2B or ITGB3 were identified as causing GT in 16 patients. We detected a total of 27 mutations in ITGA2B and ITGB3 including 17 novel missense, nonsense, frameshift and splice site mutations. In addition, three patients revealed no molecular genetic anomalies in ITGA2B or ITGB3 that could explain the suspected diagnosis of GT. We assume that these patients may harbour defects in a regulatory element affecting the transcription of these genes, or other proteins may exist that are important for activating the αIIbβ3 complex that may be affected.
Keywords: Glanzmann thrombasthenia; platelet function defect; glycoprotein αIIbβ3